Intracranial tumour haemorrhage following intravenous thrombolysis - Diehl, Christian; Haux-Nettesheim, Daniel; Sahm, Felix; Unterberg, Andreas; Beynon, Christopher (Journal of clinical neuroscience, 2016)
Intravenous administration of thrombolytic agents is considered to be contraindicated in patients with intracranial neoplasms. However, only a single case of thrombolysis-related intracranial tumour haemorrhage has been reported to our knowledge and several studies have suggested that systemic thrombolysis can be safely carried out in these patients. Here we report a patient who developed haemorrhage into a previously unknown intracranial tumour following intravenous thrombolysis for acute myocardial ST-elevation infarction. Identification of abnormal tissue during surgical haematoma evacuation initiated histopathological examination which revealed meningioma World Health Organization Grade I. Intracranial tumours may represent the causative pathology in cases of thrombolysis-related intracranial haemorrhage and this should be considered in the treatment of these patients.
Available online 29 November 2015
Gesehen am 07.02.2020